Indicators for Assessing Policy and Institutional Frameworks for Climate Smart Agriculture - Braimoh, Ademola (World Bank, Washington, DC, 2017)
Agriculture accounts for 40 percent of the land area and 70 percent of the freshwaterresources that humans use, and 24 percent of human-induced greenhouse gas (GHG)emissions. The scale of global emissions from agriculture and land-use change is increasingdue to population growth, growing consumption of meat and dairy products,and the rising use of nitrogen fertilizers,1 among other factors. Projections indicatethat emissions from human activities other than agriculture and land-use change couldincrease from 54 gigatons (Gt) of carbon dioxide equivalent (CO2-eq) to roughly 70 GtCO2-eq by 2050. To avoid dangerous global warming in which the global temperaturerises above 2 degree Celsius relative to preindustrial eras, global GHG emissions by2050 need to fall to roughly 21–22 Gt CO2-eq. Under business-as-usual practices,agriculture would contribute roughly 70 percent of these total emissions by midcentury.This implies that agriculture will need to cut its current emissions by two-thirdswhile simultaneously increasing food production.